Syntheses of biodegradable polymer networks based on polycaprolactone and glutamic acid. (19th December 2018) - Park, Soo Yong; Kim, Soo‐Yeon; Kim, Taeyoon; Ahn, Heejoon; Chung, Ildoo
Abstract : Biodegradable trifunctional oligomer was synthesized from polycaprolactone and glutamic acid and characterized by Fourier‐transform infrared (FTIR) and proton nuclear magnetic resonance ( 1 H NMR) spectroscopies. Injectable and in situ crosslinkable polymer networks were fabricated by the copolymerization of oligomer with triethylene glycol dimethacrylate (TEGDMA) and used to evaluate the initial compressive strengths, viscosities, shrinkages, thermal stabilities, and biodegradabilities in the forms of polymer network neat resin and their composites with β‐tricalcium phosphate. The initial compressive strengths (CS) values of neat resins ranged from 9.54 to 187.6 MPa. Both neat resins and composites had polymerization shrinkage ranging from 0% to 11.7%, which increased with increasing of TEGDMA contents in resin. Moreover, in polymer composite resins, shrinkage values decreased with increasing filler level from 0% to 4.6%, and exothermic evolution values decreased from 33.5°C to 29.7°C as increasing filler level. The composite with the formulation of (polycaprolactone)‐glutamate triacrylate (PCLGTA)/TEGDMA (25/75) and powder/liquid (P/L) ratio of 1.0 exhibited the highest exothermal and lowest shrinkage values. The increase of oligomer in the formulation led to an increase in viscosity.